Selection and review of measurement item to study students’ generic skills - Seri Intan Mokhtar (2012)
This study was carried out to review the GS (generic skills) instruments used for engineering students. A total of 455 respondents were involved in this study. The variables presented in this study were the information management skills, communication skill, team working skill, problem-solving skill, lifelong learning skill, technology utilization skill, critical and creative thinking skill, leadership and personal qualities. Data were analyzed descriptively for reliability (Cronbach Alpha values) and factor analysis using SPSS (Statistical Package for Social Science) 17 software. The results showed that the Cronbach Alpha was reported high and very high which was higher than 0.70. Result of factor analysis showed 10 factors solution. Each item showed a satisfactory loading of more than 0.5. Thus, the questionnaire developed was suitable to be used to study the GS acquired by engineering students in the context of education in Malaysia.